(untitled) (The Review of Diabetic Studies, 2025)
Saudi Arabia’s Vision 2030 is revolutionizing its healthcare landscape by prioritizing cutting-edge technologies to streamline operations and improve care delivery. However, as digital tools dominate the sector, the essential role of human connection remains irreplaceable. Skills such as empathy, effective communication, and cultural sensitivity are critical to fostering trust and delivering quality patient care. This paper explores the significance of soft skills in a technology-driven healthcare environment, identifies challenges in maintaining these skills, and proposes actionable strategies for their integration. By balancing innovation with compassion, Saudi Arabia can ensure a healthcare system that is both efficient and deeply human.